Effect of dietary vitamin E on physicochemical and fatty acid stability of fresh and thawed lamb. (15th January 2018) - Bellés, M.; Leal, L.N.; Díaz, V.; Alonso, V.; Roncalés, P.; Beltrán, J.A.
Highlights: The effect of vitamin E was independent of freezing. Muscle α-tocopherol concentration was 3.5-fold higher in supplemented lambs. Dietary vitamin E protected PUFA from oxidation. Lipid oxidation and colour degradation were reduced by dietary vitamin E. Abstract: This study evaluated the effect of dietary vitamin E supplementation (1000 mg of DL-α-tocopheryl acetate/kg of basal diet) on physicochemical and fatty acid stability of fresh and thawed lamb leg chops, frozen stored for 3, 6 and 9 months. Legs were chopped, modified atmosphere packaged (70% O2 /30% CO2 ) and maintained under retail conditions (4 ± 0.5 °C, with 14 h fluorescent light) for 9 days. Muscle α-tocopherol concentration was over 3.5-fold higher in supplemented samples than in control lambs. The effect of dietary vitamin E was independent of frozen storage, so these effects were analysed separately. Vitamin E supplementation reduced lipid oxidation ( P ≤ 0.001) and decreased metmyoglobin formation, leading to a more attractive colour of meat. Moreover, supplementation led to a higher percentage of polyunsaturated fatty acids. Therefore, vitamin E supplementation could be recommended for preserving either fresh or thawed lamb.